Fenestrated stent graft repair of abdominal aortic aneurysm: Hemodynamic analysis of effect of fenestrated stents on renal arteries - Sun, Zhonghua; Chaichana, T. (Korean Radiological Society, 2010)
Purpose: To investigate the hemodynamic effect of fenestrated stents on renal arteries using a fluid structure interaction method. Materials and Methods: Two representative patients with abdominal aortic aneurysm treated with fenestrated stent grafts were selected in the study. 3D realistic aorta models for the main artery branches and aneurysm were generated based on multislice computed tomographic scans from 2 patients with different aortic geometries. The simulated fenestrated stents were designed and modelled based on 3D intraluminal appearance, and placed inside the renal artery to reflect the actual patients treatment with an intra-aortic protrusion of 5.0-7.0 mm. The stent wire thickness was simulated with a diameter of 0.4 mm and hemodynamic analysis was performed at different cardiac cycles. Results: Our results showed that the effect of fenestrated stent wires on renal blood flow was minimal as the flow velocity was not significantly affected when compared to that calculated at pre-stent graft implantation, despite presence of recirculation patterns at the proximal part of the renal arteries. Wall pressure was found to decrease significantly after fenestration, however, no significant change of wall shear stress was noticed post-fenestration, although it was shown to decrease slightly at the proximal aneurysm necks. Conclusion: Our analysis demonstrates that hemodynamic effect of fenestrated renal stents on renal arteries is insignificant. Further studies are needed to investigate the effect of different lengths of stent protrusion with variable stent thicknesses on renal blood flow, which is valuable for understanding the long-term outcomes of fenestrated repair.